2019
DOI: 10.1590/1516-3180.2018.031040119
|View full text |Cite
|
Sign up to set email alerts
|

Sports participation and muscle mass affect sex-related differences in bone mineral density between male and female adolescents: A longitudinal study

Abstract: Bone health has become a concern in modern society due to the economic burden and impairment in quality of life caused by osteoporosis. 1 Osteoporotic fractures increase both healthcare costs and the risk of early mortality. 2-4 Taking into account the epidemiology of osteoporosis, women exhibit greater risk of developing osteoporosis than do men. This greater risk for the female sex is strongly determined by specific events that occur during adolescence. 5 The current literature shows how childhood and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Our results are also in agreement with several studies that have shown elevated levels of bone metabolic turnover in male athletes with different types of exercise (e. g. running, swimming, soccer) compared to female 7 18 23 26 . Nevertheless, some studies have demonstrated the modification of bone metabolic turnover with sex difference in athlete’s population 35 40 41 . Matsumoto et al 35 showed that the status of bone metabolic turnover in male judo athletes in training may be hypermetabolic, as well as that of female judo athletes with regular menses cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also in agreement with several studies that have shown elevated levels of bone metabolic turnover in male athletes with different types of exercise (e. g. running, swimming, soccer) compared to female 7 18 23 26 . Nevertheless, some studies have demonstrated the modification of bone metabolic turnover with sex difference in athlete’s population 35 40 41 . Matsumoto et al 35 showed that the status of bone metabolic turnover in male judo athletes in training may be hypermetabolic, as well as that of female judo athletes with regular menses cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, appendicular muscle mass was associated with areal bone mineral values in all studied groups in the present study. Muscle mass has been suggested to be the main pathway through which any physical exercise including athletic activity can improve part of the osteogenic process in adolescents during maturation [ 34 , 39 , 40 ]. However, although appendicular muscle mass was related to bone mineral values in SW athletes and they had the highest values of aerobic performance, their bone mineral values were lower than in the RG group.…”
Section: Discussionmentioning
confidence: 99%